Rational Choice and Developmental Influences on Recidivism Among Adolescent Felony Offenders - Fagan, Jeffrey (2007)
Recent case law and social science both have claimed that the developmental limitations of adolescents affect their capacity for control and decision making with respect to crime, diminishing their culpability and reducing their exposure to punishment. Social science has focused on two concurrent adolescent developmental influences: the internalization of legal rules and norms that regulate social and antisocial behaviors, and the development of rationality to frame behavioral choices and decisions. The interaction of these two developmental processes, and the identification of one domain of socialization and development as the primary source of motivation or restraint in adolescence, is the focus of this article. Accordingly, we combine rational choice and legal socialization frameworks into an integrated, developmental model of criminality. We test this framework in a large sample of adolescent felony offenders who have been interviewed at six-month intervals for two years. Using hierarchical and growth curve models, we show that both legal socialization and rational choice factors influence patterns of criminal offending over time. When punishment risks and costs are salient, crime rates are lower over time. We show that procedural justice is a significant antecedent of legal socialization, but not of rational choice. We also show that both mental health and developmental maturity moderate the effects of perceived crime risks and costs on criminal offending.